Impact of hepatic steatosis on mortality, hepatocellular carcinoma, end-stage liver disease and HBsAg seroclearance in chronic hepatitis B: a United States cohort study - Yendewa, George A.; Elangovan, Abbinaya; Olasehinde, Temitope; Mulindwa, Frank; Cater, Mackenzie G.; Salata, Robert A.; Jacobson, Jeffrey M. (Frontiers in Immunology, 2025)
BackgroundSteatotic liver disease (SLD) is prevalent among individuals with chronic hepatitis B virus (CHB), yet its impact on clinical outcomes remains controversial.MethodsWe used electronic health record data from 98 US healthcare-delivery systems to compare adults with (CHB-SLD) and without SLD (CHB-wo-SLD) from 2000 to 2024. We applied 1: 1 propensity score matching to balance cohorts by demographic and clinical characteristics. We further performed sensitivity analyses in the presence or absence of cirrhosis. We compared incidence rates (IR) and hazard ratios (HRs) of all-cause mortality, hepatocellular carcinoma (HCC), end-stage liver disease (ESLD) events, and detectable HBsAg and HBeAg as markers of seroclearance.ResultsAmong 124,932 individuals with CHB (12.43% CHB-SLD), there were 470,707 person-years of observations (median follow-up 2.95 years). Compared with CHB, individuals with CHB-SLD had a lower mortality risk (HR 0.44, 95% CI 0.40-0.48). Fibrosis risk was higher among those with CHB-SLD (vs CHB-wo-SLD) (HR 1.93, 95% CI 1.71-2.19); however, cirrhosis risk was comparable (HR 1.06, 95% CI 0.96-1.18) between cohorts, while HCC risk was lower in the CHB-SLD cohort (HR 0.83, 95% CI 0.70-0.96). The CHB-SLD cohort also had significantly reduced risks of ESLD events, including ascites, spontaneous bacterial peritonitis, variceal bleeding, hepatic encephalopathy, and hepatorenal syndrome (all p < 0.001). Additionally, detectable HBsAg and HBeAg IRs and HRs were lower among CHB-SLD compared to the CHB-wo-SLD cohort: 26.83 vs. 31.96 per 1,000 person-years (HR 0.80, 95% CI 0.73-0.87) and 8.52 vs. 11.36 per 1,000 person-years (HR 0.74, 95% CI 0.65-0.85), respectively. Sensitivity analyses stratified by cirrhosis status supported these findings.ConclusionCHB-SLD status was associated with more favorable outcomes, highlighting the complexity of CHB and SLD interactions.